Semiological Studies of Christian Symbolism in the Film and Series Neon Genesis Evangelion (Cinematology: Journal Anthology of Film and Television Studies, 2024)
This study analyzes the use of Christian symbolism in the film and series Neon Genesis Evangelion through a semiological approach. The research employs a semiotic analysis based on Charles Sanders Peirce's theory. The findings indicate that Neon Genesis Evangelion systematically employs Christian iconography to depict the existential transformation of humanity in an apocalyptic context. The cross, which appears in the explosions following the defeat of each Angel, serves as a marker of divine death while also signifying salvation. The Lance of Longinus, traditionally used in Christian teachings to confirm the death of Jesus on the cross, functions in the series as the primary instrument in the Third Impact event—a reality reconstruction that blurs the boundaries between destruction and re-creation. Additionally, the use of Angel names derived from the Christian angelic hierarchy reinforces the spiritual narrative that intertwines religious mythology with the fictional world-building of Neon Genesis Evangelion. Through this analysis, the study asserts that Christian symbolism in Neon Genesis Evangelion is not merely aesthetic or decorative but constructs a complex dialectic concerning human existence, suffering, and the pursuit of salvation. The series demonstrates how religious symbols can be adapted in popular media to convey broader narratives about the meaning of existence and human destiny within the landscape of contemporary culture.